Author Correction: Polygonal motion and adaptable phototaxis via flagellar beat switching in the microswimmer Euglena gracilis. Issue 12 (December 2018) - Tsang, Alan; Lam, Amy; Riedel-Kruse, Ingmar
In the version of this Article originally published, the angular oscillation of amplitude in Fig. 4a was incorrectly labelledζ ; it should have beenξ . Also, the blue line in the top-right corner of Fig. 6d should not have been dash-dotted but solid. These have now been corrected in all versions of the Article.